Genes and training for athletic performance - Hopkins, W. G. (Sportscience, 2001)
Genes are responsible for about half the variation in physical performance between individuals in the population. Genes also account for half the variation in the response to physical training. Genes are probably even more important than training in explaining differences in performance between athletes. Talent identification and selecting an appropriate partner are therefore logical approaches to creating elite athletes. What are the practical implications of the fact that athletes are born and made? Here are a few: - Failure to win is not necessarily failure to train right: you can always blame genes, amongst other things. - Talent identification is not a futile exercise, because differences in physical ability or in the response to training in young people are not due simply to differences in prior training. Talent spotters should take into account the sporting prowess of the family of a prospective young athlete. - Genotyping of prospective athletes will become an option when performance or injury genes have been identified, but many will regard the practice as unethical. - If you want your kids to be great athletes, marry a great athlete.